A GEANT4 based simulation framework for the large area muon telescope of the GRAPES-3 experiment. (1st March 2023) - Varsi, F.; Ahmad, S.; Chakraborty, M.; Chandra, A.; Dugad, S.R.; Goswami, U.D.; Gupta, S.K.; Hariharan, B.; Hayashi, Y.; Jagadeesan, P.; Jain, A.; Jain, P.; et al.
Abstract: The GRAPES-3 experiment located in Ooty, India, samples the electron and muon components in extensive air showers using an array of plastic scintillator detectors and a muon telescope (G3MT) consisting of proportional counters to study the composition of primary cosmic rays (PCRs) as well as γ -ray sources in the TeV–PeV energy range. The G3MT is designed with an appropriate mass absorber to shield the electromagnetic and hadronic components in the shower and to detect muons above 1 GeV×sec( θ ) energy, incident from a zenith angle θ . We developed a simulation framework based on the GEANT4 toolkit to evaluate the response of shower particles such as muons, γ -rays, electrons and hadrons in the G3MT. We discuss the geometric modeling of the G3MT using GEANT4 starting with the proportional counter. We estimated the punch-through contribution of hadrons in the G3MT. We compare the simulated muon multiplicity distributions with the observed ones assuming PCR composition from a four population supernova remnant acceleration model namely H4a.